Apport De La Stratigraphie Sequentielle Dans L’evolution Jurassique Du Moyen Atlas Central (Maroc) - Benjelloun Faiza; Fedan Bouazza; Anjjar Ahmed; Lahrach Abderrahim; Boukhir Mohammed; Chaouni Abdel-Ali (European Scientific Journal, ESJ, 2017)
The Jurassic evolution of the central Middle Atlas is governed by various factors (climate and eustatism). The use of the concepts of sequential stratigraphy in the regions of Tagnamas and Boulemane allowed to interpret the geometry and the vertical sequence of sedimentary sets. Twelve sequences are identified and delimited by sedimentary discontinuities. The lithostratigraphic division adopted in this study is synchronous with the coastal aggradation charter of Haq & al. (1987 & 1988) and Rioult & al. (1991). The correlations on a regional scale, between different Jurassic lithostratigraphic units is possible, whose the major factors controlling the evolution of intraplate basins are climate and eustatism.